Bacterial spectrum and proportion of multidrug-resistant bacteria in clinical samples from a regional hospital in Lambaréné, Gabon (2017–2023): Implications for antimicrobial resistance surveillance and public health - Maradona Daouda Agbanrin; Bayode Romeo Adegbite; Christiane Sidonie Gouleu; Sam O’neilla Oye Bingono; Jean Ulrich Muandze-Nzambe; Augustin B. Boueya; Lea Dane Damo; Lubin M. Etougou Ovono; Marina H. Biteghe Nsole; Prince Gedeon Manouana; Peter. Gottfried Kremsner; Frieder Schaumburg; et al. (PLOS Global Public Health, 2026)
This cross-sectional study investigates the spectrum and proportion of multidrug-resistant (MDR) bacteria isolated from clinical samples processed at the regional microbiology laboratory of Lambaréné, Gabon. Bacteriological results from 2017 to 2023 were retrospectively analysed to assess the rates of non-susceptibility among the most common isolates from urine, blood, stool, and swabs (wound, urethral, ear, and throat). Antimicrobial susceptibility testing and interpretation were performed according to Clinical Laboratory Standards Institute (CLSI) guidelines.A total of 5,401 cultures were reviewed, with 1,050 yielding clinically relevant bacterial isolates. The most frequently identified pathogens were Escherichia coli (273/1050; 26%), Staphylococcus aureus (192/1050; 18%), β-hemolytic Streptococci (160/1050; 15%), and Klebsiella pneumoniae (69/1050; 6.6%). Urine samples predominantly yielded E. coli and K. pneumoniae , while S. aureus was most common in wound and blood cultures. Overall, 23% (242/1050) of isolates were classified as MDR, with E. coli accounting for 40% (96/1050). The proportion of ESBL producers among Enterobacterales was 10% (55/522). Resistance to third-generation cephalosporins was notably high, especially among K. pneumoniae (28/69; 41%) and E. coli (34/273; 13%). Methicillin-resistant S. aureus (MRSA) represented 12% (22/192) of S. aureus isolates; 5.5% (58/1050) of isolates belong to the WHO critical-priority pathogen group.Clinical microbiology data from Lambaréné indicate that urinary infections are mainly associated with E. coli , whereas S. aureus predominates in wound swabs and blood cultures. The detection of WHO critical-priority pathogens in this setting supports the need for sustained microbiological monitoring and locally adapted measures to improve antibiotic use and infection prevention.